Environmental commitment and Islamic bank performance: Does management quality matter? - Fakhrunnas, Faaza; Anto, MB Hendrie (Faculty of Business & Economics, Universitas Islam Indonesia, 2025)
Purpose – This study investigates the impact of Islamic banks' environmental commitment on their financial performance. In addition, the moderating role of management quality is employed to assess whether it affects the nexus of environmental commitment and Islamic banks’ financial performance. Methodology – The sample of the study consists of 32 Islamic banks from 12 countries with sufficient environmental commitment reports from 2016 to 2023. A panel data approach is adopted to estimate the models in this study, namely the random effects model (REM), 2-Stage Least Squares (2SLS), and Least Squares Dummy Variable Corrected (LSDVC).Findings – The findings reveal that Islamic banks' commitment to environmental activities supports their financial performance. In addition, the management quality of Islamic banks moderates the relationship between environmental commitment and financial performance. The findings of this study are robust after conducting estimations to check the consistency of the results using several econometric scenarios. Implication – The findings imply the urgency to embrace, practice, and develop environmental commitment in Islamic banking. It can be implemented by policymakers and regulators to spur and demand that Islamic banks have sufficient environmental commitment while operating them. Originality – This study contributes to the precise examination of inconclusive findings on the nexus between environmental commitment and financial performance in global Islamic banks. Moreover, it highlights the role of management quality in the nexus between environmental commitment and financial performance, which remains understudied in prior literature.